Redox-Active Species in Carbon Nanotubes - Townsend, William (2023)
The work in this thesis investigates single-walled carbon nanotubes (SWNTs) as host for redox active materials towards energy applications. SWNTs provide a template for the formation of unique, nano-dimension morphologies of encapsulated materials, with extremely high surface area to volume ratios.